2016
DOI: 10.1111/njb.00535
|View full text |Cite
|
Sign up to set email alerts
|

Elevational gradient and vegetation‐environmental relationships in the central Hyrcanian forests of northern Iran

Abstract: Tertiary‐relict Hyrcanian (Caspian) forest along the shores of the southern Caspian Sea is a center of biodiversity. Still, there is little information on plant diversity patterns in this area. This study evaluated plant diversity, variation in life forms, and geographical distribution of the zonal vegetation types and their relationships with environmental variables, in the educational and experimental forest of Kheyrudkenar, an important protected area in the central Hyrcanian forest of northern Iran. For th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
4
12
0
Order By: Relevance
“…Neither slope inclination nor altitude affect the proportion of endemism (PE 5,6 ) on the studied rocks. This result is consistent with a previous study in the Hyrcanian area (Moradi et al ) and suggests that endemic and subendemic plants distribute evenly over all habitat and topographical situations of the area. The proportion of endemism of the studied rock outcrops is 17.5% (36 species), which is close to that of othe similar ecosystems in the Hyrcanian highlands (Ejtehadi et al ).…”
Section: Discussionsupporting
confidence: 93%
“…Neither slope inclination nor altitude affect the proportion of endemism (PE 5,6 ) on the studied rocks. This result is consistent with a previous study in the Hyrcanian area (Moradi et al ) and suggests that endemic and subendemic plants distribute evenly over all habitat and topographical situations of the area. The proportion of endemism of the studied rock outcrops is 17.5% (36 species), which is close to that of othe similar ecosystems in the Hyrcanian highlands (Ejtehadi et al ).…”
Section: Discussionsupporting
confidence: 93%
“…In our study area, among the environmental variables analyzed, soil properties and type, as well as altitude, were found to be the main factors determining the occurrence of plant species. Similar relationships have previously been indicated by Moradi et al (2016) for the vegetation of northern Alborz Ranges, and by Zare-Maivan et al (2014, 2015a, 2015b) for vegetation of the Parvar Protected Area in south-cental Alborz ranges of the Semnan province. In their extensive research, Moradi et al (2016) demonstrated that constrained (CCA) and unconstrained (DCA) ordination analyses both revealed an almost identical pattern in the floristic composition, sugesting that there are two main gradients in the Hyrcanian forests.…”
Section: Discussionsupporting
confidence: 85%
“…The Central Alborz Ranges is a vast region that extends east-west along the Caspian Sea, the northern side receiving relatively much precipitation while the southern side is dry due to the barrier effect of the Alborz Mountain Ranges. Moradi et al (2016) investigated the elevation -environmental and vegetation relationships in the central Hyrcanian forests of the northern side of the central Alborz Ranges. No similar study has been conducted on the southern side of the Alborz Ranges, which is mostly composed of calcium carbonate (lime) and calcium sulfate (gypsum) bedrocks.…”
Section: Introductionmentioning
confidence: 99%
“…Elevation is a key variable affecting species diversity in mountains, as has been established in numerous studies (Fetene et al , Muhumuza and Byarugaba ). Likewise, Fallahchai () and Moradi et al () found a negative correlation between elevation above sea level and species richness in the Hyrcanian forests. The negative effects of slope on species diversity in the current investigation were obvious, which could be related to soil erosion, water drainage and unfavorable conditions for plant growth (Hall ).…”
Section: Discussionmentioning
confidence: 83%
“…The Hyrcanian forests provide a refuge for broad‐leaved deciduous trees including Arcto–Tertiary relicts such as Zelkova carpinifolia, Parrotia persica, Pterocarya fraxinifolia and Quercus castaneifolia , and Asian subtropical trees such as Gleditsia caspica and Albizia julibrissin (Djamali et al ). Recently, several studies relating vegetation and ecological species groups to environmental variables have been carried out within the Hyrcanian forests (Esmailzadeh and Hosseini , Jalilvand et al , Kooch et al , Salehi et al , Naqinezhad et al , Eshaghi Rad and Banj Shafiei , Kialashaki and Shabani , Kooch , Pourbabaei and Haghgooy , Naqinezhad et al , Pourbabaei and Abedi , Adel et al , Bazdid Vahdati et al , Moradi et al ). The present study aims to identify the main ecological species groups in the Surash forest as a pristine pilot study site in the western Hyrcanian area, based on TWINSPAN classification, and to evaluate the relationships between environmental factors (elevation, slope, aspect and soil variables) and ecological species groups using multivariate analyses (DCA and CCA).…”
mentioning
confidence: 99%